2017
DOI: 10.3390/s17040834
|View full text |Cite
|
Sign up to set email alerts
|

Modeling DGNSS Pseudo-Range Correction Messages by Utilizing Satellite Repeat Time

Abstract: We developed and validated a pseudo-range correction (PRC) modeling system that can prevent degradation of positioning accuracy even in situations where one cannot obtain PRC messages for Differential Global Navigation Satellite System (DGNSS). A PRC modeling scheme was devised based on the repeat time of GNSS satellites and previously-collected PRC data. The difference between the modeled and real PRC values observed at the reference station showed a bias error of about ±1.0 m and a root mean square error (RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Researchers using predicted PRC demonstrated that for DGPS/DBeiDou horizontal positioning errors were at one meter level of accuracy. Such a solution would unquestionably be very helpful to keep DGNSS positioning during outages of correction data [11]. Considering the ambiguity resolution, estimation, and analysis of code biases is also very important in this process, depending on the pseudorange method.…”
Section: Dgps (Differential Globalmentioning
confidence: 99%
“…Researchers using predicted PRC demonstrated that for DGPS/DBeiDou horizontal positioning errors were at one meter level of accuracy. Such a solution would unquestionably be very helpful to keep DGNSS positioning during outages of correction data [11]. Considering the ambiguity resolution, estimation, and analysis of code biases is also very important in this process, depending on the pseudorange method.…”
Section: Dgps (Differential Globalmentioning
confidence: 99%
“…In the technique of positioning BSSD, code observations are differenced from GNSS satellites which are tracked down by one receiver installed onboard an aircraft (Krasuski, 2017b). The technique of DGNSS positioning allows differencing code observations between the GNSS reference station and a rover receiver installed onboard an aircraft (Sohn et al , 2017). On the other hand, the technique of RTK-OTF position makes it possible to differentiate phase observations between the GNSS reference station and a rover receiver mounted onboard an aircraft (Tsujii et al , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Among quoted techniques, the DGNSS technique using pseudorange correction (PRC) has also been widely used in a number of research fields improving real-time positioning accuracy in cheap receivers. Positioning accuracy obtained by researchers using predicted PRC demonstrated that for DGPS and DBeiDou horizontal errors were at the one meter level, which definitely would be very useful to continue DGNSS positioning during correction data outages [ 14 ]. The estimation and analysis of code biases is also essential for ambiguity resolution when depending on the pseudorange method.…”
Section: Introductionmentioning
confidence: 99%